Blue‐Emissive Cobalt(III) Complexes and Their Use in the Photocatalytic Trifluoromethylation of Polycyclic Aromatic Hydrocarbons. (4th June 2018) - Pal, Amlan K.; Li, Chenfei; Hanan, Garry S.; Zysman‐Colman, Eli
Abstract: Room‐temperature luminescent Co III complexes (1 and 2 ) are presented that exhibit intense ligand‐to‐metal and ligand‐to‐ligand charge transfer absorption in the low‐energy UV region ( λ abs ≈360–400 nm) and low‐negative quasi‐reversible reduction events ( E 1/2 (red) =−0.58 V and −0.39 V vs. SCE for 1 and 2, respectively). The blue emission of 1 and 2 at RT is due to the large bite angles and strong σ‐donation of the ligands, the combined effect of which helps to separate the emissive 3 LMCT (triplet ligand‐to‐metal charge transfer) and the non‐emissive 3 MC (triplet metal‐centered) states. 1 and 2 were found to be powerful photo‐oxidants ( E Co III * / Co II =2.26 V and 2.75 V vs. SCE of 1 and 2, respectively) and were used as inexpensive photoredox catalysts for the regioselective mono(trifluoromethylation) of polycyclic aromatic hydrocarbons (PAHs) in good yields (ca. 40–58 %).